1999
DOI: 10.1152/jappl.1999.87.4.1476
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb unweighting decreases ecNOS gene expression and endothelium-dependent dilation in rat soleus feed arteries

Abstract: We tested the hypothesis that hindlimb unweighting (HLU) and the associated reduction in soleus muscle blood flow causes decreased expression of endothelial cell nitric oxide synthase (ecNOS) mRNA and protein and attenuated endothelium-dependent vasodilator responses in rat soleus feed arteries (SFA). Male Sprague-Dawley rats were exposed to HLU (n = 12) or cage control (Con; n = 12) conditions for 14 days. At the end of this period, SFA were isolated, removed, and cannulated with two glass micropipettes for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 36 publications
13
81
0
Order By: Relevance
“…soleus muscle blood flow induced by hindlimb unweighting are associated with reductions in eNOS expression and ACh-induced dilation in SFA (15,18). Although previous studies to determine the effect of aging on skeletal muscle blood flow did not reveal age-related decrements in resting blood flow to the rat hindlimb (9,13), the effect of aging on intraluminal shear stress within SFA is not known.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…soleus muscle blood flow induced by hindlimb unweighting are associated with reductions in eNOS expression and ACh-induced dilation in SFA (15,18). Although previous studies to determine the effect of aging on skeletal muscle blood flow did not reveal age-related decrements in resting blood flow to the rat hindlimb (9,13), the effect of aging on intraluminal shear stress within SFA is not known.…”
Section: Discussionmentioning
confidence: 91%
“…Differences in eNOS and SOD-1 protein expression were assessed in single feed arteries (matched for diameter and length) by using immunoblot analysis as described previously in detail (15,28). eNOS protein expression was evaluated with a monoclonal antibody (1:1,600; catalog no.…”
Section: Quantification Of Enos and Sod-1 Expressionmentioning
confidence: 99%
“…Data on the effect of inactivity are controversial. Previous animal studies (23,40,51) mimicking physical inactivity by hindlimb unloading report inconsistent results with some studies showing a decreased nitric oxide synthase (NOS) gene expression and concomitant attenuated endothelium-dependent vasodilator responses, whereas other studies (38,50) report an upregulation of the NOS system. In humans, a recent bed-rest study demonstrated that plasma nitrate and nitrite concentration, an indicator of endogenous NO production, was decreased after 14 days of bed-rest immobilization (25).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the decreased NOS signaling is related to diminished expression of endothelial NOS (eNOS) or superoxide dismutase (SOD), relative differences in eNOS and SOD-1 protein content were assessed in gastrocnemius first-order arterioles by Western blot as described previously (31). eNOS protein content was evaluated with a monoclonal antibody (1:1,600; catalog no.…”
Section: Study 3: Endothelium-dependent and -Independent Vasodilationmentioning
confidence: 99%